Employment: The Root of The Problem and the Solution in an Islamic Perspective - Miptahudin, Iip (Journal of Economicate Studies, 2022)
Employment is everything related to labor at the time before, during and after the completion of the employment period, both in the work that produces goods and work in the form of. From the aspect of labor law is a private legal field that has a public aspect, because although the working relationship is made based on the freedom of the parties, but there are a number of provisions that must be subject to the provisions of the government in the sense of public law Almost in all countries today,  employment or labor problems always grow and develop, both in developed and developing countries. Indonesia is also facing a variety of serious issues in employment issues. The root of employment problems lies in the fulfillment of life's needs. The responsibility of the state is to provide guarantees of fulfillment of basic needs to the people, and Islam has set clearly and in detail about the laws related to ij?rat al-aj?r (employment contracts).